Ovarian activity and plasma concentrations of progesterone and estradiol during pregnancy in jennies - Meira, Cezinande de [UNESP]; Ferreira, JCP; Papa, Frederico Ozanam [UNESP]; Henry, M. (Elsevier B.V., 1998)
The objectives of this study were to determine ovarian activity (with ultrasound) and plasma concentrations of progesterone and estradiol during pregnancy in jennies. There was considerable ovarian activity during the second month of pregnancy. Secondary corpora lutea (total of 2 to 7 per jenny) were formed (mainly by luteinization) starting on Day 41.8 +/- 1.0 (range Days 38 to 46; ovulation = Day 0). The echogenicity of the primary and secondary corpora lutea gradually decreased during pregnancy. Plasma progesterone concentrations increased between Days 0 and 10 (0.9 and 19.9 ng/mL, respectively), gradually decreased to Day 30 (12.1 ng/mL), increased between Days 30 and 40 (plateau, at approximately 17 ng/mL), gradually declined from Days 110 to 160 (nadir of approximately 6 ng/mL), and remained nearly constant until increasing again just before parturition. Plasma estradiol concentrations increased gradually from Day 65, peaked (1.2 ng/mL) on Day 165 (greater than or equal to 1 ng/mL on Days 150 to 210), and decreased thereafter, with very low concentrations during the last 20 d before parturition. Ovarian function and hormone profiles were generally similar to those previously reported during pregnancy in mares. (C) 1998 by Elsevier B.V.
Keywords: pregnancy; donkey; progesterone; estradiol; ultrasonography